Amyloid β Enhances Typical Rodent Behavior While It Impairs Contextual Memory Consolidation - Karla Salgado-Puga; Roberto A. Prado-Alcalá; Fernando Peña-Ortega (Behavioural Neurology)
Alzheimer’s disease (AD) is associated with an early hippocampal dysfunction, which is likely induced by an increase in soluble amyloid beta peptide (Aβ). This hippocampal failure contributes to the initial memory deficits observed both in patients and in AD animal models and possibly to the deterioration in activities of daily living (ADL). One typical rodent behavior that has been proposed as a hippocampus-dependent assessment model of ADL in mice and rats is burrowing. Despite the fact that AD transgenic mice show some evidence of reduced burrowing, it has not been yet determined whether or not Aβ can affect this typical rodent behavior and whether this alteration correlates with the well-known Aβ-induced memory impairment. Thus, the purpose of this study was to test whether or not Aβ affects burrowing while inducing hippocampus-dependent memory impairment. Surprisingly, our results show that intrahippocampal application of Aβ increases burrowing while inducing memory impairment. We consider that this Aβ-induced increase in burrowing might be associated with a mild anxiety state, which was revealed by increased freezing behavior in the open field, and conclude that Aβ-induced hippocampal dysfunction is reflected in the impairment of ADL and memory, through mechanisms yet to be determined.